Implementasi Kebijakan Pelayanan Administrasi Kependudukan Daring (Sobat Dukcapil) Di Dinas Kependudukan Dan Pencatatan Sipil Kota Tangerang Tahun 2023 - Kurnia Sari, Septia; Handayani, Riny; Rahmawati (CV. Multi Kreasi Media, 2024)
Public services must be able to continue running under any conditions, including during the Covid-19 pandemic. The Tangerang City Population and Civil Registration Service has begun implementing online population administration services through the Sobat Dukcapil Application to limit services directly to the Tangerang City Population and Civil Registration Service Office. Initially, services through the Dukcapil Friends Application did not run effectively due to a discrepancy between theory and actual events. The purpose of this research is to determine whether the implementation of population administration services on the Sobat Dukcapil Application at the Tangerang City Population and Civil Registration Service Office is running effectively. This research theory uses policy implementation theory according to Van Meter and Van Horn which states that there are 6 variables that form a bond between policy and performance in policy implementation analysis. This research method uses descriptive qualitative research methods. The results of this research show that in 2020-2022 it turns out that the Sobat Dukcapil Application service does not involve the APBD because there is still a lack of special training for Sobat Dukcapil Application service operators. The socialization carried out is also less intensive because it is mostly done through social media rather than directly in each region. The implementation of the drive thru service has not been effective because people still prefer to put their vehicles in the parking lot to collect their population documents.